Control of mechatronic systems - Güvenç, Levent; Güvenç, Bilic Aksun; Demirel, Burak; Emirler, Mümin Tolga (IET control, robotics and sensors series ;, 2017)
This book introduces researchers and advanced students with a basic control systems background to an array of control techniques which they can easily implement and use to meet the required performance specifications for their mechatronic applications.